KEY FUNDAMENTAL ASPECTS FOR MAPPING AND ASSESSING ECOSYSTEM SERVICES: PREDICTABILITY OF ECOSYSTEM SERVICE PROVIDERS AT SCALES FROM LOCAL TO GLOBAL. - Zurlini, G.; Petrosillo, I.; Aretano, R.; Castorini, I.; D'Arpa, S.; De Marco, A.; Pasimeni, M. R.; Semeraro, T.; Zaccarelli, N. (Annali di Botanica, 2014)
How an apparent static and ordered landscape condition in social ecological landscapes (SELs), can be made sustainable in terms of maintenance and improvement of the provision of ecosystem services (ESs) in face of unpredictable disturbance and change? Our contribution to the Mapping and Assessment of Ecosystem Services (MAES) working group is to advance some recommendations on how to approach the dynamic analysis of complex adaptive systems to improve ecosystem resilience, habitat connectivity and the delivery of ESs. We show exemplary cases where we utilize the NDVI provided by remote sensing to evaluate land cover transformations and processes and ES provisioning. We focus on NDVI because it allows the supply of information on net primary production, i.e., the energetic foundation of nearly all ecosystems and that provides the basis of most of ESs. The use of spectral entropy, and nonlinear analysis of spatial temporal dynamics to investigate trajectory predictability of SELs provide very useful insight into the dynamics of SELs and can assist in the characterization of the links between land cover patterns with ecological processes to support more reliable assessments and accountings of ESs.